If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -8c + -8c + -4b + -4b = 0 Reorder the terms: 8 + -4b + -4b + -8c + -8c = 0 Combine like terms: -4b + -4b = -8b 8 + -8b + -8c + -8c = 0 Combine like terms: -8c + -8c = -16c 8 + -8b + -16c = 0 Solving 8 + -8b + -16c = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8b + -8 + -16c = 0 + -8 Reorder the terms: 8 + -8 + -8b + -16c = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -8b + -16c = 0 + -8 -8b + -16c = 0 + -8 Combine like terms: 0 + -8 = -8 -8b + -16c = -8 Add '16c' to each side of the equation. -8b + -16c + 16c = -8 + 16c Combine like terms: -16c + 16c = 0 -8b + 0 = -8 + 16c -8b = -8 + 16c Divide each side by '-8'. b = 1 + -2c Simplifying b = 1 + -2c
| 5x-20=-3x+20 | | x-5-7=2(x+2) | | 12(x-3)-32=5(13+x) | | 92+53+115+2x+3x=540 | | 0=7/6x+6 | | 2(-8+6x)=-4 | | 2(5x+7)=-42+26 | | 5(-6x+3)=15 | | 1x-3=-4x+37 | | 1=7/6x+6 | | -1(5x-3)=1 | | 2x+42=-4x | | -5x+6-x=-6 | | 2x-8=-3x+22 | | 6x+7(2-x)=14-9x-8 | | Y=7/6(0)+6 | | 3x-9=-4x+19 | | 1x-4=-4x+36 | | 3(x+5)(x-10)=7 | | 79-17/8 | | 8=-3x+4x+1 | | 3(c-5)+4c(c-5)= | | 11x-7x=4 | | 3(x-4)=2(5x-11) | | 6x-3(1)=0 | | -7x-9=54 | | 4x+48=-2x | | 5x-15=-2x+20 | | 2x-6=-4x+42 | | x=5::3:2.5 | | 6(0)-3y=0 | | 4x-12=-4x+28 |